Supervisors’ Academic Supervising Behaviors and Graduate Students’ Academic Thriving: The Mediating Roles of Admiration and Task Engagement - Yang Wu; Zhenzhen Chen; Dongjing Zhang (Behavioral Sciences)
This study aims to examine the association between supervisors’ academic supervising behaviors and academic thriving of graduate students, as well as its underlying mechanisms—the mediating effects of admiration and task engagement. A sample of 1792 graduate students in central China was recruited to participate in this study (52.3% male; Mage = 23.266, SDage = 5.435). The results show that the supervisors’ academic supervising behaviors are positively associated with graduate students’ self-reported academic thriving; furthermore, the mediating effects of both admiration and task engagement in the relationship are also significant, which consist of three mediating paths—the separate mediating effects of admiration and of task engagement, and serial mediation involving both admiration and task engagement. This study found that frequent supervising behaviors may promote academic thriving in graduate students through increasing students’ admiration for supervisors and task engagement. The findings not only contribute to our understanding of graduate students’ academic thriving and its mechanisms, but also add to the literature on promoting a positive psychological state of graduate students as well as graduate education.